Digital photography hacks - Story, Derrick (O'Reilly, 2004)
Your digital camera is more than new incarnation of your old film camera. Yes, it still produces photos, but it also offers new outlets for creativity, including instant gratification of seeing your photos now, the ability to experiment without worrying about expense, the technology to fine-tune your photos with advanced professional techniques, and the means to share your work instantaneously with anyone, anyplace in the world. It's no wonder that digital cameras are outselling traditional cameras for the first time ever. But the question most digital camera users ask is this, "How do I get from taking 'decent' photos to doing the things I'd really like to do? How do I tap into that potential?" Digital Photography Hacks is your passport to taking the kind of digital photos you've always aspired to. Written by Derrick Story, photographer and author of Digital Photography Pocket Guide and other books, it goes beyond the standard fare of most digital photography books--such as camera basics, understanding memory cards, and when to use a flash--to the things that professional photographers have learned through thousands of shots' worth of experience, years of experimentation, and fiddling and hacking. The book includes a foreword by photographer Rick Smolan, author of America 24/7. With exquisite, full-color photos throughout, the book presents a collection of tips, tricks, and techniques for photographers ready to move beyond the basics. And if you don't have the latest in digital camera photography, this book will show you how to extend the life and functionality of your existing camera. All the hacks in the book are platform-agnostic, designed for use on both Mac on Windows-based computers. You'll find 100 proven techniques in the areas of: Daytime and nighttime photo secrets Flash magic Digital camera attachments The computer connection Photoshop magic Fun photo projects Camera phone tricks This book is for the photographer you are now, and the one you want to be. Digital Photography Hacks is for the creative adventurer who resides in each of us.